Validitas Smart Pop Up Book Berbasis Gusjigang Sebagai Edukasi Seksualitas Siswa Tunagrahita SLBN Kaliwungu - Sari, Rina Kartika; Indrawati, Marita Puji; Insani, Muhammad Afdholil Kholiqoh; Nafidzah, Bashroh; Rahman, Firdaus Noorhadi; Masfuah, Siti (PGSD Universitas Muria Kudus, 2025)
This study aims to describe the validity of Gusjigang-based Smart Pop Up Book media.This study is part of research and development consisting of preliminary study, development, and validation stages. At this validation stage, 2 experts validated the developed media. Validity assessment consists of media and material aspect validation. The experts consist of media and material developer concept experts. Data collection techniques use non-test techniques. The instruments used are media validation sheets and material validation sheets. Data analysis uses quantitative descriptive data analysis techniques.The results of media validation that have been carried out by media experts are obtained from the first and second validators with an average value of 4.15 which means it is feasible to be implemented for students. In addition, the results of material validation from both validators obtained an average value of 4.10 which means it is feasible to be implemented. Results Based on data analysis, it can be concluded that the Gusjigang-based Smart Pop Up Book media is valid and can be used in student learning